2010
DOI: 10.1590/s0100-736x2010001100002
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos clínico-patológicos e imuno-histoquímicos de equídeos infectados pelo vírus da raiva

Abstract: Foram analisados 14 equídeos (13 equinos e 1 muar) com diagnóstico clínico e histológico de raiva provenientes de quatro regiões do Brasil. O curso clínico médio foi de quatro dias de evolução, incluindo incoordenação motora, paralisia dos membros pélvicos, paresia dos membros torácicos e decúbito. Os achados histopatológicos caracterizaram-se por meningoencefalite e meningomielite não supurativa com infiltrado perivascular linfoplasmocitário. Corpúsculos de Negri foram observados em 64,28% (9/14) dos casos, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
3
5
0
7
Order By: Relevance
“…46 IHC, in the present study, revealed the presence of viral antigen in all 33 rabies cases; this is in agreement with another work 40 in which the viral antigen was detected in all (39) of the cases analyzed. Additionally, 22 of the cases analyzed in our study (66.6%) were positive for rabies as detected by DFAT; this frequency is similar to that found in another study 31 in which 55% of the samples from horses diagnosed with rabies were positive as detected by DFAT. These data show that complete agreement between tests may not happen for all samples.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…46 IHC, in the present study, revealed the presence of viral antigen in all 33 rabies cases; this is in agreement with another work 40 in which the viral antigen was detected in all (39) of the cases analyzed. Additionally, 22 of the cases analyzed in our study (66.6%) were positive for rabies as detected by DFAT; this frequency is similar to that found in another study 31 in which 55% of the samples from horses diagnosed with rabies were positive as detected by DFAT. These data show that complete agreement between tests may not happen for all samples.…”
supporting
confidence: 90%
“…9,16,42 Additionally, multifocal hemorrhagic areas were observed in the spinal cords of all horses, sometimes macroscopically, which corroborates findings of other authors. 13,31 The exact mechanism by which RABV causes neuronal lesions and ultimately death is unknown. One hypothesis is marked viral-induced downregulation of genes in the brain.…”
mentioning
confidence: 99%
“…This is because in horses, in addition to the CNS samples required for collection in ruminants, sampling of cervical, thoracic and lumbar spinal cord segments is essential for the diagnosis of most neurological diseases, since lesions are often located in this region (Rech & Barros, 2015). If samples are not collected and stored correctly, laboratory diagnosis will not be successful, leading to inconclusive results (Pedroso et al 2010;Peixoto et al, 2000;Rech & Barros, 2015).…”
Section: Important Topics To Consider In Brazilmentioning
confidence: 99%
“…According to Pedroso et al (2010), the number of positive cases is great because samples are not sent to laboratory diagnosis and research about such a disease in this species is scarce (Lima et al, 2005).…”
Section: Resultsmentioning
confidence: 99%